THEORETICAL PROBLEMS ASSOCIATED WITH THE LEGAL CONCEPT OF TERM “GENOCIDE” - Gabrieljans, Armens (Administrative and Criminal Justice, 2015)
The aim of this article is to define and analyze the theoretical problems associated with historical and legal characteristics of the concept of genocide. In this article is reviewed the history of creation and introduction into international law of the term “genocide”.